Consumer Based-Brand Equity - Ekinci, Yuksel (My University, 2014)
Research Objectives The objectives of this study are to: - Assess external validity of Nam et al.’s (2011) CBBE model in different culture (Turkey) and new service context (fashion retailing). - Compare validity of Nam et al.’s (2011) CBBE model with the brand equity model introduced by Yoo and Donthu (2001). - Expand the Nam et al.’s (2011) model by introducing “brand awareness”.
Keywords: Marcas registradas; Moda